The good bank: preference of banking institutions based on perceptions of corporate environmental and social causes - Gaspar, Augusta D.; Pinto, Joana Carneiro (Frontiers in Behavioral Economics, 2024)
Introduction This study aims to contribute to understanding factors that explain consumers' preferences for banking institutions. We specifically explored the roles of Corporate Social Responsibility (CSR)—targeted primarily at Environmental causes and secondarily at Social causes—on corporate image (CI), consumer satisfaction (CS) and consumer loyalty (CL). We tested whether integrating a CSR description with an emphasis on environmental causes into the bank marketing strategy would positively affect CI, CS and CL. We also inspected the effect of online banking vs. direct human contact, and perception of price fairness, as well as that of the consumers' demographic variables. Methods A survey was carried out online, with 322 international respondents recruited through social networks. Participants were randomly directed to one of eight different bank conditions, each combining descriptions where Environmental and social CSR, Price fairness, and direct human contact with the clients varied. After reading the bank description participants filled out a questionnaire that addressed their perception of the bank's CI and their projections of CS and CL. Results and discussion Results indicated that participants favored the banks that included CSR as part of their description, with the perception of price fairness being the second critical factor in the respondents' CI, CS, and CL. Direct human contact vs. remote banking did not play a role in the participant's ratings of the bank, which is in line with more current studies. We concluded that businesses in the banking sector enhance their global reputation when investing in environmental and social CSR.